Pendapatan Usahatani Kacang Tanah Varietas Hibrida dan Varietas Lurik di Desa Parang Kecamatan Banyakan Kabupaten Kediri: Pendapatan Usahatani Kacang Tanah Varietas Hibrida dan Varietas Lurik di Desa Parang Kecamatan Banyakan Kabupaten Kediri - Nico Nur Juan; Navita Maharani; Vifi Nurul Choirina (JURNAL ILMIAH AGRINECA, 2026)
The purpose of this study was to determine the factors that influence the farming business, income, and feasibility of hybrid and striped peanut farming in Parang Village, Tarokan District, Kediri Regency. The sampling method in this study was the Stratified Random Sampling method which aims to ensure that all strata in the population have an equal opportunity to be represented in the study, so that the results obtained are more accurate and can describe the actual conditions in the field. The data analysis methods used were income analysis, farming feasibility analysis. The results showed that the production factors used in hybrid and striped peanut farming are land, seleds, fertilizers, pesticides, technology, and labor. Income from hybrid and striped peanut farming is different. Hybrid peanut farming produces lower income than striped peanut farming. The averagel production of hybrid peanuts is 3,751 kg/ha, with revenuel of Rp. 7,881,604.00/ha. Meanwhile, the average production of striped peanut varieties is 3,656 kg/Ha with an income of Rp. 13,741,696.00/Ha. The R/C Ratio obtained from hybrid peanut variety is 1.43, while the R/C Ratio from striped peanut variety is 1.72. This shows that the R/C Ratio of striped peanut variety is higher than the R/C Ratio of hybrid peanut variety.